Refining Islamic Eco-Philosophy: A Comparative Assessment of Ikhwan al-Shafa’s Cosmology - Lestari, Ayu; Malik, Muhammad Khoirul; Kharisman, Hadi (FIKRAH, 2026)
The current global environmental crisis is seen as rooted in an anthropocentric paradigm that desacralizes nature, thereby breaking the spiritual connection between humans and the environment. This study aims to analyze the ecological principles in the cosmological theory of Ikhwan al-Shafa and its relevance to modern ecological discourse. The research was conducted using a qualitative approach, drawing on primary and secondary literature. This article uses an analytical-philosophical method to interpret the primary texts of Rasail with a comparative-critical reading to compare the findings of the thought of the Ikhwan al-Shafa with key concepts of modern ecology. Researchers found a principle of unity among all the elements of the universe and a universal soul. This universal soul gives life and controls all the elements of the universe. Although the Ikhwan al-Shafa was a group of 10th-century classical Muslim philosophers, its thinking remains relevant to modern ecological discourse. This research position seeks to refine previous studies that have only addressed the content of Ikhwan al-Shafa’s cosmological theory and its implications for ecological understanding. This research contributes to providing a solid ethical-theological foundation for resolving the environmental crisis.